Prevalence of diarrhoea among under five children in India and its contextual determinants: A geo-spatial analysis - Koustav Ghosh; Atreyee Sinha Chakraborty; Mithun Mog (Elsevier, 2021)
Background: Diarrheal diseases which is one of the leading reason behind global mortality and morbidity is more threatening for infants and young children. Childhood diarrhoea is becoming increasingly prevalent disease in developing countries like India. Moreover, it is a major cause of malnutrition that contributes towards third major cause of under 5 mortalities. This has raised a serious concern in the domain of public health. Objectives: The present study attempts to identify the spatial prevalence and clustering of diarrhoea in India based on National Family and Heath Survey (NFHS-4, 2015-16) and also tries to identify the association of prevalence of diarrheal disease among under 5 children with socio-economic factors. Methods: The study applies spatial analysis software i.e ArcGIS 10.8 and GeoDa 1.18 including Moran's index and logistics regression to show the spatial prevalence and auto-correlation of diarrhoea among neighbourhood districts and their contextual determinants. Findings: The study finds a total of 71 districts belong to the hot spot area are mostly from central and eastern costal part of India. Analysis of socio-economic determinants show prevalence of diarrhoea among under 5 children is higher in rural areas, among children not staying in Pacca house, living with unimproved sanitation facilities, belonging to under privileged community (highest among OBC followed by SC/STs), children of younger mothers (<25 years) and "poor' households considering the wealth index. Conclusion: The study recommends to target hot-spot districts with high prevalence of diarrhoea and policy level interventions like improved sanitation to reduce the risk of childhood diarrhoea.